Interactive Multimedia Development with CSCL Learning Strategy Assisted by Concept Map for Concept Understanding of Elementary School Students - Mei, Robbych Dewanti Wulan; Kuswandi, Dedi; Praherdhiono, Henry (IJIE (Indonesian Journal of Informatics Education), 2023)
Elementary School students are Alpha generation children who understand technology. With today's increasingly rapid technological developments, concept maps can be used to support learning with computer technology by utilizing the CSCL model so that students can interact and collaborate anytime and anywhere online. For this reason, interactive multimedia development was carried out with CSCL learning strategies assisted by Concept Map for concept understanding of elementary school students. This development research aims to produce interactive multimedia to improve the understanding of grade 5 elementary school students in aspects of knowledge, skills, and attitudes. We use the Lee & Owens model to test the product's feasibility. In addition, to determine the improvement in learning outcomes of grade 5 elementary school students, an N-Gain Score normality test and a hypothesis test were carried out using paired sample t-test on pretest and post-test value data. The developed product is interactive multimedia with CSCL learning strategies assisted by Concept Map, and it is equipped with content in the form of reading materials, learning videos, and evaluation tests. The results of interactive multimedia validation produce excellent criteria based on material aspects, learning media aspects, and learning design. The response of grade 5 elementary school students received excellent criteria for the feasibility of multimedia learning as a learning medium. Based on the results of statistical tests, it was concluded that there was an increase in learning outcomes after using interactive multimedia with CSCL learning strategies assisted by Concept Map.